Harnessing TikTok for English Learning: Addressing Digital Literacy Gaps Among Indonesian High School Students - Khairani Putri Salsya; Alvi Raihan Utami; Intan Hamzah; Salsabila Elysia (ELT (English Language Teaching Prima Journal), 2026)
Despite the widespread use of social media among Indonesian youth, digital literacy and English language proficiency remain unevenly developed. This study explores how TikTok, as a popular short-form video platform, can serve as a medium for English language learning and digital literacy enhancement among Indonesian high school students. Employing a qualitative case study approach, the research involved digital diaries, semi-structured interviews, and focus group discussions with students from two public senior high schools. The findings indicate that students engage with TikTok daily, frequently encountering English-language content such as vocabulary tips, dialogue-based skits, lyric challenges, and storytelling videos. This exposure supports incidental learning and fosters motivation; however, most students engage passively with the content and show limited ability to critically assess or reflect on the material. While TikTok offers authentic and engaging opportunities for language input, it does not inherently promote deeper digital literacy without pedagogical scaffolding. The study emphasizes the importance of guided educational strategies that incorporate popular digital platforms like TikTok to support both language acquisition and critical digital literacy. It also calls for curricular reforms to better align with students’ digital practices and suggests further research into structured integrations of social media in formal language instruction. Keywords: TikTok, English language learning, digital literacy, Indonesian high school students, social media-based learning, EFL, informal learning environments.